Enter the name of the publisher of the previously issued instance of this item - Sologub, Yuriy; Kazantseva, Katerina; Protas, Andrey (My University, 2018)
Financial sector, as well as all other aspects of business, has not escaped the introduction of IT-technologies. Not only have these technologies accelerated all transactions, but also made them relatively cheap and in-stant. If earlier payments were primarily conducted only in traditional currencies by banks and other relevant entities, recently the Bitcoin and other similar cryptocurrencies took its place as a universal currency. This article is devoted to the topical matter of cryptocurrencies, their functions and mechanisms of emission.
Keywords: currency system; cryptocurrency; bitcoin; decentralized system; the risk of inflation; кафедра туристичного та готельного бізнесу